2018
DOI: 10.5606/tr-ent.2018.35229
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric analysis of laryngeal anatomy: A cadaveric study

Abstract: Objectives: This study aims to describe morphometric measurements of the laryngeal framework and discuss their implications for phonosurgery among Turkish subjects. Patients and Methods:Larynges from 40 male and 20 female fresh cadavers were extracted during autopsy in a forensic science institution between January 2015 and December 2015. Measurements were taken of the length of membranous and cartilaginous vocal fold (mVF, cVF), width and thickness of VF (wVF, tVF), anterior and posterior subglottic distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
1
16
1
Order By: Relevance
“…Among the laryngeal cartilages, the thyroid cartilage seems to exhibit the greatest differences in size among individuals, sexes, and races. 27,28 In the present study, the distance from the mark to the upper border of the thyroid cartilage was significantly different between men and women. The reason for this is considered to be the differences in the sizes of the thyroid bones.…”
Section: Discussioncontrasting
confidence: 53%
“…Among the laryngeal cartilages, the thyroid cartilage seems to exhibit the greatest differences in size among individuals, sexes, and races. 27,28 In the present study, the distance from the mark to the upper border of the thyroid cartilage was significantly different between men and women. The reason for this is considered to be the differences in the sizes of the thyroid bones.…”
Section: Discussioncontrasting
confidence: 53%
“…It is a well‐delimited elliptical shape in newborns through school‐aged children, and its boundaries become asymmetrical and murkier in teenagers and young adults. Averaging almost 1/3 of the VF mucosa thickness, this area correlates with the elliptical description of the maculae flavae, 4,54 the fibrous synthesis region of the vocal ligament reported in histopathologic studies and often characterized as an intertwined network of collagenous and elastic fibers 10,55,56 . This low scattering region may represent the VF elastic fibers running between the anterior and posterior maculae flavae.…”
Section: Discussionsupporting
confidence: 66%
“…Our values are matching to the other studies done for this parameter. 2,3,9 However in a study on Brazilian population, no morphometric changes between sexes was observed. 10 Most of the relevant anatomic details are based on Western population and the studies pertaining to Indian population are extremely limited, especially for measurement of thyroid cartilage thickness.…”
Section: Thyroid Anglementioning
confidence: 89%
“…And was lesser than similar parameter measured in other races such as Nigerians and Europeans. 6,8,9 Length of Inferior Horn: The mean length of inferior horn in males was longer in right than the left one while in females the reverse was true. The findings in the present study were in consonance with other studies done in Indian population.…”
Section: Length Of Superior Horn Of Thyroid Cartilagementioning
confidence: 96%
See 1 more Smart Citation